Air quality monitoring system (back end) using FPGA: article / Amrillah Najmin - Najmin, Amrillah (2009)
This paper is about the development of Air Quality Monitoring System using FPGA. This system is developed in order to monitor air pollution at our country. This system consists of software and hardware part. For the software part, the Graphical User Interface (GUI) is developed using JAVA tools as a medium to activate the sensor through the Field Programmable Gate Array (FPGA) Quartus II Board and the output data from the sensors will be displayed at PC. For the hardware part, a circuit, consists of temperature and humidity sensors, is activated and processed by the program written in VHDL and implemented on Altera CycloneII FPGA. The GUI menu, the FPGA and the sensors circuit are connected together to develop the complete system of the air quality monitoring system.